University Fairness Questionnaire (UFair): Development and Validation of a German Questionnaire to Assess University Justice—A Study Protocol of a Mixed Methods Study - Herr, Raphael; Deyerl, Veronika; Hilger-Kolb, Jennifer; Diehl, Katharina (International Journal of Environmental Research and Public Health, 2022)
Distress is a widespread phenomenon in the general population, but also among university students, associated with poorer learning success and negative health consequences. A source of distress might be the experience of injustice. Theoretical and empirical work in the area of perceived fairness in the workplace (“organizational justice”) has shown that perceived unfairness is related to various stress indicators and health outcomes. Preliminary evidence indicates that unfairness matters not only in the work context but also in the university context. However, an adapted and validated tool to assess perceived unfairness in the university context is hitherto missing. The goal of the proposed project is therefore to adapt the construct of organizational justice to the university context and to develop a corresponding questionnaire by means of established scientific procedures. An exploratory sequential mixed-methods design is applied in which qualitative and quantitative methods are combined. A valid and practicable measurement instrument (“UFair” University Fairness Questionnaire) will be developed and tested, and the relationship with various health outcomes will be examined. The UFair questionnaire will be made available free of charge to other researchers.
CRIS-Team Scopus Importer:2022-12-23
Keywords: development; fairness; health; justice; mixed-methods; questionnaire; stress; students; university; validation